Caenorhabditis elegans SET1/COMPASS Maintains Germline Identity by Preventing Transcriptional Deregulation Across Generations - Robert, Valérie J.; Knutson, Andrew K.; Rechtsteiner, Andreas; Garvis, Steven; Yvert, Gaël; Strome, Susan; Palladino, Francesca (Frontiers in Cell and Developmental Biology, 2020)
Chromatin regulators contribute to the maintenance of the germline transcriptional program. In the absence of SET-2, the C. elegans homologue of the SET1/COMPASS H3 Lys4 (H3K4) methyltransferase, animals show transgenerational loss of germline identity, leading to sterility. To identify transcriptional signatures associated with progressive loss of fertility, we performed expression profiling of set-2 mutant germlines across generations. We identify a subset of genes whose misexpression is first observed in early generations, a step we refer to as priming; their misexpression then further progresses in late generations, as animals reach sterility. Analysis of misregulated genes shows that down-regulation of germline genes, expression of somatic transcriptional programs, and derepression of the X chromosome are concurrent events leading to loss of germline identity in both early and late generations. Notably, the transcription factor LIN-15B, the C/EBP homologue CEBP-1, and TGF-beta pathway components are upregulated in set-2 mutant germlines and depletion of cebp-1 and TGF-beta/Smad signaling by RNAi delays the onset of sterility, showing that they individually contribute to maintenance of germ cell identity and fertility. Our approach therefore identifies genes and pathways whose misexpression across generations contributes to the eventual loss of germ cell fate. More generally, our data show how loss of a chromatin regulator leads to transcriptional changes that are amplified over generations, ultimately leading to loss of appropriate cell fate.